Neurobrucellosis due to Brucella ceti ST26 in Three Sowerby's Beaked Whales (Mesoplodon bidens). (January 2021) - Davison, Nicholas J.; Brownlow, Andrew; Doeschate, Mariel Ten; Dale, Emma-Jane; Foster, Geoffrey; Muchowski, Jakub; Perrett, Lorraine L.; Rocchi, Mara; Whatmore, Adrian M.; Dagleish, Mark P.
Summary: Fatal meningoencephalitis due to Brucella ceti infection has been described in striped dolphins ( Stenella coeruleoalba ), Atlantic white-sided dolphins ( Lagenorhynchus acutus ), short-beaked common dolphins ( Delphinus delphis ) and long-finned pilot whales ( Globicephala melas ), which are all within the family Delphinidae. We report B. ceti -associated neurobrucellosis in three juvenile male Sowerby's beaked whales ( Mesoplodon bidens ) that all had typical lesions of lymphocytic meningoencephalitis, which increased in severity from rostral to caudal regions of the brain. In two cases there was loss of ependymal cells lining the cerebral ventricular system, with large numbers of lymphocytes in the underlying neuropil. This finding suggests that B. ceti gains access to, and multiplies in, the cerebrospinal fluid, and confirms that this is the sample of choice for bacteriological recovery of the causative organism. These findings expand the increasing range of cetaceans susceptible to neurobrucellosis to members of the family Ziphiidae.